Wage Elasticity of the Teacher Supply in Switzerland - Stefan C. Wolter; Stefan Denzler (Institute for the Study of Labor (IZA), 2003)
In order to learn more about the wage elasticity of the teacher supply in Switzerland, this paper estimates wages for teachers and non-teachers. The data used are ten surveys of graduates of all Swiss universities for the period of 1981-1999. The data allows us to estimate the wage elasticity for entry wages of upper secondary school teachers. In the cases examined, the wage differential is highly significant and shows a wage elasticity for the teacher supply of 0.12% to 0.18%. This elasticity is substantially lower than what has been found in the literature for other countries. It is probably due to the fact that teachers? salaries are generally high in Switzerland - teachers here enjoy a positive wage differential over those in other occupations, the opposite of what is normally the situation elsewhere.
Keywords: I2; J24; J45; 330; wage elasticity; labour supply; teachers; university graduates; Switzerland; Lehrkräfte; Arbeitsangebot; Lohn; Elastizität; Schätzung; Schweiz